2023
DOI: 10.1186/s12879-023-08335-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the etiology of acute febrile illness: a prospective clinic-based study in Uganda

Abstract: Background Historically, malaria has been the predominant cause of acute febrile illness (AFI) in sub-Saharan Africa. However, during the last two decades, malaria incidence has declined due to concerted public health control efforts, including the widespread use of rapid diagnostic tests leading to increased recognition of non-malarial AFI etiologies. Our understanding of non-malarial AFI is limited due to lack of laboratory diagnostic capacity. We aimed to determine the etiology of AFI in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The findings of the Acute Febrile Illness (AFI) study including the detection of LDV have been reported previously [ 10 , 11 ]. Here we focus on the clinical presentation of the LDV patient.…”
Section: Resultsmentioning
confidence: 85%
“…The findings of the Acute Febrile Illness (AFI) study including the detection of LDV have been reported previously [ 10 , 11 ]. Here we focus on the clinical presentation of the LDV patient.…”
Section: Resultsmentioning
confidence: 85%
“…For East Sub-Saharan Africa, annual morbidity of 91,100 cases per 100,000 population has been reported [6]. In Uganda, Leptospira exposure has been shown in febrile patients from geographically distinct areas [7][8][9][10]. Domestic animals, particularly cattle and pigs are speculated as the source of these human Leptospira exposures [7,8,10], despite evidence of exposure in other main reservoirs such as wildlife [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, Leptospira exposure has been shown in febrile patients from geographically distinct areas [7][8][9][10]. Domestic animals, particularly cattle and pigs are speculated as the source of these human Leptospira exposures [7,8,10], despite evidence of exposure in other main reservoirs such as wildlife [11]. This is possible since human-wildlife interactions are less common than interactions with domestic animals.…”
Section: Introductionmentioning
confidence: 99%
“…AFS diagnosis requires a comprehensive approach to each patient; the wide-ranging causes require detailed clinical methodologies and the diagnostic tests to support them. Diagnosis and treatment are adversely affected in regions where access to specialized tests is not immediately available [10,11].…”
Section: Introductionmentioning
confidence: 99%